Patient and provider perceptions of a peer-delivered intervention ('Khanya') to improve anti-retroviral adherence and substance use in South Africa: a mixed methods analysis - Rose, Alexandra L; Belus, Jennifer M; Hines, Abigail C; Barrie, Issmatu; Regenauer, Kristen S; Andersen, Lena S; Joska, John A; Ciya, Nonceba; Ndamase, Sibabalwe; Myers, Bronwyn; Safren, Steven A; Magidson, Jessica F (CAMBRIDGE UNIV PRESS, 2022)
BACKGROUND: Despite a high prevalence of problematic substance use among people living with HIV in South Africa, there remains limited access to substance use services within the HIV care system. To address this gap, our team previously developed and adapted a six-session, peer-delivered problem-solving and behavioral activation-based intervention (Khanya) to improve HIV medication adherence and reduce substance use in Cape Town. This study evaluated patient and provider perspectives on the intervention to inform implementation and future adaptation. METHODS: Following intervention completion, we conducted semi-structured individual interviews with patients (n = 23) and providers (n = 9) to understand perspectives on the feasibility, acceptability, and appropriateness of Khanya and its implementation by a peer. Patients also quantitatively ranked the usefulness of individual intervention components (problem solving for medication adherence 'Life-Steps', behavioral activation, mindfulness training, and relapse prevention) at post-treatment and six months follow-up, which we triangulated with qualitative feedback to examine convergence and divergence across methods. RESULTS: Patients and providers reported high overall acceptability, feasibility, and appropriateness of Khanya, although there were several feasibility challenges. Mindfulness and Life-Steps were identified as particularly acceptable, feasible, and appropriate components by patients across methods, whereas relapse prevention strategies were less salient. Behavioral activation results were less consistent across methods. CONCLUSIONS: Findings underscore the importance of examining patients' perspectives on specific intervention components within intervention packages. While mindfulness training and peer delivery models were positively perceived by consumers, they are rarely used within task-shared behavioral interventions in low- and middle-income countries.